CAMPUS-TO-WORKSHOP ADAPTATION GAPS IN PRE-SERVICE VOCATIONAL TEACHER EDUCATION - Ahmad Surur Ramziqi; Dian Julianto Wahyudi; Muhammad Yudi Syaputra; Ramadhan Dwi Widodo; Ulfi Ayu Masluchi; Zaky Fatkhur Naufal Afif Malik; Zulkifli Zulkifli; Hananda Riski Ramadani (Universitas Islam Negeri Mataram, 2026)
Preparing vocational teacher candidates requires more than strengthening technical knowledge and digital competence; it also requires readiness to teach in authentic workshop environments. This study examines pre-service vocational teacher students’ adaptation during a Teaching Assistance programme in the Machining Engineering expertise concentration at SMK Islam 1 Blitar, Indonesia. Using an evaluative qualitative case study design, data were collected from four mentor teachers who supervised seven Mechanical Engineering Education students during school placement. Structured interviews and student performance assessment documents were analysed across four domains: material mastery, facility and tool mastery, classroom or workshop management, and learning administration. The findings show an uneven readiness profile. Students demonstrated stronger readiness in facility and tool mastery, particularly in digital and laboratory-based learning such as CAD/GTM, while their readiness was less stable in workshop management and school-based learning administration. The study identifies a campus-to-workshop adaptation gap, where university-based preparation supported digital and theoretical readiness but did not fully transfer into conventional machine practice, safety-oriented workshop control, pedagogical authority, and administrative flexibility. The study concludes that vocational Teaching Assistance should be designed as a structured transition process supported by workshop-based microteaching, machine familiarisation, shared administrative templates, and mentor-guided reflection.